The Evaluation of a Custom-Made Insole on Foot Plantar Pressures in an Individual with Flexible Flatfoot: Single Case Study - Khosravi Farsani , Mobina; Daryabor, Aliyeh; Rezaei , Mehdi; Okhovatian, Farshad (Journal of Clinical Physiotherapy Research, 2020)
Flexible flatfoot is one of the most common types of foot disorders. The aim of the present study was to assess the effectiveness of a custom-made 3D printed insole for a subject with flexible flatfoot. The subject was a 10-year-old boy who had the flexible flatfeet. The custom-made foot insoles for both feet were made using the 3D scanner for both feet. The feet data was evaluated after a 8-month use of insole compared with before wearing. The findings revealed that foot type improved in the subject after the 8-month use of the insoles. Right foot in dynamic surface and both feet in static surfaces changed from light flat to normal type. It seems using the 3D printed insoles can be useful in reducing the foot plantar pressure and the surface in individuals with flexible flatfoot. Keywords: Orthotic, Insole, Flatfoot, Pressure